2016
DOI: 10.2337/db16-0107
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Contribution of GLP-1 to Mediating Insulinotropic Effects of DPP-4 Inhibition With Vildagliptin in Healthy Subjects and Patients With Type 2 Diabetes Using Exendin [9-39] as a GLP-1 Receptor Antagonist

Abstract: We quantified the contribution of GLP-1 as a mediator of the therapeutic effects of dipeptidyl peptidase 4 (DPP-4) inhibition (vildagliptin) by using the GLP-1 receptor antagonist exendin in patients with type 2 diabetes and in healthy subjects. Thirty-two patients with type 2 diabetes and 29 age-and weight-matched healthy control subjects were treated in randomized order with 100 mg once daily vildagliptin or placebo for 10 days. Meal tests were performed (days 9 and 10) without and with a high-dose intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 27 publications
6
49
1
1
Order By: Relevance
“…The elegant study by Nauck et al (9) reported in this issue of Diabetes provides important insights regarding the mechanisms underlying glucose lowering by DPP-4 inhibition that are consistent with, and complimentary to, outcomes reported by Aulinger et al (10) (Fig.1). In the study by Nauck et al (9), a total of 32 patients with type 2 diabetes managed by diet or metformin and 29 healthy control subjects received vildagliptin 100 mg or placebo for 10 days in a crossover design.…”
Section: Dpp-4 Inhibition and The Known Unknownsupporting
confidence: 70%
See 4 more Smart Citations
“…The elegant study by Nauck et al (9) reported in this issue of Diabetes provides important insights regarding the mechanisms underlying glucose lowering by DPP-4 inhibition that are consistent with, and complimentary to, outcomes reported by Aulinger et al (10) (Fig.1). In the study by Nauck et al (9), a total of 32 patients with type 2 diabetes managed by diet or metformin and 29 healthy control subjects received vildagliptin 100 mg or placebo for 10 days in a crossover design.…”
Section: Dpp-4 Inhibition and The Known Unknownsupporting
confidence: 70%
“…Hence, the effect of DPP-4 inhibition on gastric emptying is of interest. Although Nauck et al (9) found no effect measured by a breath test (9), there is probably a modest slowing (10,19), albeit much less than that induced by short-acting GLP-1 agonists (16). Gastric emptying is also a determinant of the glycemic response to DPP-4 inhibition (19,20), and strategies that slow gastric emptying and stimulate GLP-1 secretion, such as whey preloads (19), potentiate glucose lowering.…”
Section: Dpp-4 Inhibition and The Known Unknownmentioning
confidence: 99%
See 3 more Smart Citations